Health Literacy and Income Mediate Racial/Ethnic Asthma Disparities - Ryan G. Seibert; Michael R. Winter; Howard J. Cabral; Michael S. Wolf; Laura M. Curtis; Michael K. Paasche-Orlow (Health Literacy Research and Practice, 2019)
Background: Health literacy and socioeconomic status (SES) are associated with both race/ethnicity and asthma outcomes. The extent to which health literacy and SES mediate racial/ethnic asthma disparities is less clear. Objective: To determine if health literacy and SES mediate racial/ethnic asthma disparities using advanced mediation analyses. Methods: A secondary analysis was performed using a Chicago-based longitudinal cohort study conducted from 2004 to 2007 involving 342 adults age 18 to 41 years with persistent asthma. Phone interviews were conducted every 3 months assessing asthma quality of life (AQOL; scored 1–7, with 7 being the highest) and asthma-related health care use measures. Structural equation models assessed mediation of race/ethnicity effects on AQOL and health care use through health literacy and SES. Covariates in the best-fit model included sex, year and season of interview, and cigarette smoking. Key Results: The study sample was 77.8% female, 57.3% African American/non-Hispanic, and 28.7% Hispanic. Race/ethnicity was significantly associated with AQOL and asthma-related emergency department (ED) visits, but only indirectly, through the effects of health literacy and income. Compared with White/non-Hispanics, African American/non-Hispanics and Hispanics had significantly higher odds of low health literacy and lower income. Low health literacy was associated with significantly lower AQOL scores (β = −0.24, 95% confidence interval (CI) [−0.38, −0.10]) and higher odds of an ED visit (adjusted odds ratio = 1.24, 95% CI [1.07, 1.43]). Increasing income was associated with significantly higher AQOL scores (β = 0.18, 95% CI [0.08, 0.28]) and lower odds of an ED visit (adjusted odds ratio = 0.88, 95% CI [0.80, 0.97]). Conclusions: The relationships between race/ethnicity and several asthma outcomes were mediated by health literacy and income. Interventions to improve racial/ethnic asthma disparities should target health literacy and income barriers.